Bacterial diversity and community structure of banana rhizosphere in Orang Asli fields and commercial plantations - Lee, Jason Yee Neng; Tan, Irene Kit Ping (Penerbit Universiti Kebangsaan Malaysia, 2018)
Bacteria play an important roles in the soil ecosystem and in the rhizosphere, they are intricately linked to nutrient content and its accessibility to plants, plant protection and sometimes pathogenicity. Banana grows well in the tropics and it is popularly grown in Orang Asli (OA) (indigenous people) settlements. Banana is also grown in commercial plantations. In traditional planting practices, the OA do not add pesticide nor fertilizer to their crops which are planted for selfsustenance mainly. On the other hand, fertilizer and pesticide are added to commercial banana plantations to maximise yield. Rhizosphere bacteria from the banana plant, Pisang Nipah, grown in OA fields and commercial plantations were identified by clone library construction of the 16S rRNA gene. This was to determine whether farming practices influenced the bacterial community in the banana plant rhizosphere. Acidobacteria, Proteobacteria and Actinobacteria were found in all the soil. Other common phyla found in some soil (but not all) were Nitrospirae, Firmicutes, Bacteroidetes, Chloroflexi, Verrumicrobia, Gemmatimonadetes and Cyanobacteria. The bacterial diversity was a little more diverse in the OA fields than the commercial plantations. The latter had higher contents of nitrogen, phosphorus and potassium. These could have exerted selective pressure to reduce the bacterial diversity in the commercial plantations.